An exploratory survey of Trypanosoma cruzi infection in carnivores (urocyon cinereoargenteus and spilogale angustifrons) of yucatan, Mexico - Interian-Aguiñaga, Jesus Guadalupe; Escobedo-Ortegón, Francisco Javier; Guillermo-Cordero, José Leonardo; Ruiz-Piña, Hugo Antonio (Brazilian Journal of Global Health, 2022)
OBJETIVO: Foi realizado estudo exploratório para determinar a infecção por Trypanosoma cruzi na raposa cinza (U. cinereoargenteus) e no gambá manchado do sul (S. angustifrons) em Yucatán, México. MÉTODOS: Usamos amostras de vários órgãos (coração, músculo esquelético, rim, baço, fígado, esôfago e estômago), correspondente a indivíduos de raposa cinzenta e gambá manchado, capturados no peridomicílio de oito localidades rurais de Yucatán entre o período de 1990-2008. A presença de DNA de T. cruzi em amostras de tecido foi determinada pelas técnicas PCR e exames histopatológicos. RESULTADOS: Todos os indivíduos estudados tinham pelo menos uma amostra de tecido com DNA de T. cruzi. O esôfago (9/13), o coração (7/13) e o músculo esquelético (6/13) foram os órgãos com maior frequência de DNA de T. cruzi. Não foram encontrados ninhos de amastigotas, no entanto, a observação microscópica revelou lesões características da infecção por T. cruzi, como infiltração inflamatória por linfócitos e histiocitos com ou sem necrose de células cardiomiócitos, e proliferação de fibrocitos, fibroblastos e fibras de colágeno (fibrose). CONCLUSÕES: Os resultados confirmam que esses dois carnívoros selvagens são hospedeiros naturais do T. cruzi em Yucatán, México. O comportamento sinantrópico desses dois mamíferos em Yucatán torna necessário focar estudos futuros sobre seu papel dentro do ciclo de transmissão peridomiciliar rural do T. cruzi na Península de Yucatán. DESCRITORES: Urocyon, Spilogale, Carnívoros, Trypanosoma cruzi, PCR, Histopatologia, Yucatán. ABSTRACT OBJECTIVE: We carried out an exploratory study to determine the infection with Trypanosoma cruzi in the gray fox (U. cinereoargenteus) and the southern spotted skunk (S. angustifrons) in Yucatan, Mexico. METHODS: We used samples from various organs (heart, skeletal muscle, kidney, spleen, liver, esophagus, and stomach) corresponding to individuals of gray fox and spotted skunk, captured in the peridomicile of eight rural localities of Yucatan between the period 1990–2008. The presence of T. cruzi DNA in tissue samples was determined by PCR technique and histopathology study. RESULTS: All the individuals studied had at least one tissue sample with T. cruzi DNA. The esophagus (9/13), heart (7/13), and skeletal muscle (6/13) were the organs with the highest frequency of T. cruzi DNA. No nests of amastigotes were found, however, microscopic observation revealed lesions characteristic of T. cruzi infection, such as inflammatory infiltrate by lymphocytes and histiocytes with or without necrosis of cardiomyocytes cells, and proliferation of fibrocytes, fibroblasts and collagen fibers (fibrosis). CONCLUSIONS: Our results confirm that these two wild carnivores are natural hosts for T. cruzi in Yucatan, Mexico. The synanthropic behavior of these two mammals in Yucatan makes it necessary to focus future studies on their role within the rural peridomiciliary transmission cycle of T. cruzi in the Yucatan Peninsula. DESCRIPTORS: Urocyon, Spilogale, Carnivores, Trypanosoma cruzi, PCR, Histopathology, Yucatan.